Galectin-4 N-Terminal Domain: Binding Preferences Toward A and B Antigens With Different Peripheral Core Presentations - Quintana, Jon I.; Delgado, Sandra; Núñez-Franco, Reyes; Cañada, F. Javier; Jiménez-Osés, Gonzalo; Jiménez-Barbero, Jesús; Ardá, Ana (Frontiers in Chemistry, 2021)
The tandem-repeat Galectin-4 contains two different domains covalently linked through a short flexible peptide. Both domains have been shown to bind preferentially to A and B histo blood group antigens with different affinities, although the binding details are not yet available. The biological relevance of these associations is unknown, although it could be related to its attributed role in pathogen recognition. The presentation of A and B histo blood group antigens in terms of peripheral core structures differs among tissues and from that of the antigen-mimicking structures produced by pathogens. Herein, the binding of the N-terminal domain of Gal-4 towards a group of differently presented A and B oligosaccharide antigens in solution has been studied through a combination of Nuclear Magnetic Resonance (NMR), Isothermal Titration Calorimetry (ITC) and molecular modeling. Our data allow to identify the specific effects that subtle chemical modifications within this antigenic family have in the binding to Gal-4N in terms of affinity and intermolecular interactions, providing a structural-based rationale for the observed trend in the binding preferences.